Implicit and explicit social mentalizing: dual processes driven by a shared neural network - Van Overwalle, Frank; Vandekerckhove, Marie (Frontiers in Human Neuroscience, 2013)
Recent social neuroscientific evidence indicates that implicit and explicit inferences on the mind of another person (i.e., intentions, attributions or traits), are subserved by a shared mentalizing network. Under both implicit and explicit instructions, ERP studies reveal that early inferences occur at about the same time, and fMRI studies demonstrate an overlap in core mentalizing areas, including the temporo-parietal junction and the medial prefrontal cortex. These results suggest a rapid shared implicit intuition followed by a slower explicit verification processes (as revealed by additional brain activation during explicit versus implicit inferences). These data provide support for a default-adjustment dual-process framework of social mentalizing.